Partnerships in applying new and innovative technology - Elser, Paul G., author; Barnett, Mark T., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
The Roza Irrigation District (Roza), in the Yakima Valley of Washington State, received only 37 percent of its water right entitlement in the 1994 and 2001 irrigation seasons due to its junior water status in the basin. A reduction in water allocation of this magnitude places a great deal of stress on farmers and their crops, and hinders the District's ability to deliver water. Faced with having to operate with less than 50 percent (600 cfs) of design flow, Roza has become one of the most progressive irrigation districts in the Pacific Northwest with respect to water conservation by applying new and innovative technology. Since 1991, Roza has developed numerous partnerships to help fund and apply resourceful technology to water conservation measures. Initially, Armtec and UMA introduced the automated single-leaf over shot gate, which was applied to numerous main canal checks to provide constant level control for pipeline turnouts and pumping plants. One of Roza's most successful partnerships has been with the United States Bureau of Reclamation (Bureau) Water Conservation Field Services Program in Yakima, and Aqua Systems 2000 Inc. (AS2I) from Lethbridge, Alberta, Canada. The partnership began in 1997 when an existing flashboard check structure was replaced with an automated Langemann gate. The success of this project, cost shared with the Bureau, prompted Roza to discontinue building new multi-bay single-leaf over shot structures and building or retrofitting eight structures with a single Langemann gate, the largest being 24-feet wide. The partnership with the Bureau and AS2I expanded to include Supervisory Control and Data Acquisition (SCADA) on two existing main canal checks and a re-regulation reservoir. These innovative projects include flow control using undershot gates, spill flow monitoring using ultrasonic level technology, downstream canal level control using a variable speed pump and modulating valve, and remote communications via spread spectrum radio, dedicated phone line, and cellular digital modem technology. The SCADA system was recently expanded with the incorporation of an Acoustic Doppler Flow Meter (ADFM) downstream of the diversion point. In addition, Roza also partnered with MagnaDrive, Inc. (MagnaDrive) and AS2I to demonstrate variable speed pump control on an existing pumping plant. MagnaDrive supplied a magnetic coupler rather than a variable frequency drive (VFD), and AS2I provided the controls design and software to the flow control project. The success of these projects has enabled Roza to reduce low-end operational flows from 600 cfs to 280 cfs in water short years and still provide reliable service to its water users.
USCID/EWRI conference
Roza Irrigation District
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.